2021
DOI: 10.1097/wco.0000000000000907
|View full text |Cite
|
Sign up to set email alerts
|

Insular seizures and epilepsies: Ictal semiology and minimal invasive surgery

Abstract: Purpose of review The increased identification of seizures with insular ictal onset, promoted by the international development of stereo-electroencephalography (SEEG), has led to the recent description of larger cohorts of patients with insular or insulo-opercular epilepsies than those previously available. These new series have consolidated and extended our knowledge of the rich ictal semiology and diverse anatomo-clinical correlations that characterized insular seizures. In parallel, some experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
2
14
0
3
Order By: Relevance
“…The left dendrogram shows features of the patients with insulo-opercular epilepsy and on the right features of the patients with mesiotemporal epilepsy [34]. The second most frequent seizure manifestation was somatosensory (including perioral and throat sensations) and autonomic symptoms (including bradycardia) [16,17,34]. Progression to bilateral tonic-clonic seizures was less frequent in other series than in our cohort, which may be partially related to tapering of antiepileptic drugs during video-EEG recordings in our patient sample.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The left dendrogram shows features of the patients with insulo-opercular epilepsy and on the right features of the patients with mesiotemporal epilepsy [34]. The second most frequent seizure manifestation was somatosensory (including perioral and throat sensations) and autonomic symptoms (including bradycardia) [16,17,34]. Progression to bilateral tonic-clonic seizures was less frequent in other series than in our cohort, which may be partially related to tapering of antiepileptic drugs during video-EEG recordings in our patient sample.…”
Section: Discussionmentioning
confidence: 61%
“…2 Results of the cluster analysis. The left dendrogram shows features of the patients with insulo-opercular epilepsy and on the right features of the patients with mesiotemporal epilepsy [34]. The second most frequent seizure manifestation was somatosensory (including perioral and throat sensations) and autonomic symptoms (including bradycardia) [16,17,34].…”
Section: Discussionmentioning
confidence: 99%
“…Though none of the patients in this series underwent LITT, there is growing evidence that this technique may yield good outcomes. Our group recently published a review of minimally invasive techniques and found that 58% of patients having undergone LITT in the available literature (a total of 38 patients) had Engel class I outcomes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insuläre Epilepsien sind ein besonders herausforderndes Thema unter den pharmakoresistenten Epilepsien [4]. Ihre besondere anatomische Lage am Grund der Sylvischen Furche bedeckt vom frontalen, temporalen und parietalen Operculum sowie den Ästen der A. cerebri media (ACM) macht den Zugang zur Insel schwierig und morbiditätsbehaftet [18]. Trotzdem können ein gutes Ergebnis und eine hohe Rate an Anfallsfreiheit postoperativ erreicht werden, wobei häufig eine invasive Ableitung der Insel notwendig ist [2, 7-9, 14,18,21].…”
unclassified
“…Ihre besondere anatomische Lage am Grund der Sylvischen Furche bedeckt vom frontalen, temporalen und parietalen Operculum sowie den Ästen der A. cerebri media (ACM) macht den Zugang zur Insel schwierig und morbiditätsbehaftet [18]. Trotzdem können ein gutes Ergebnis und eine hohe Rate an Anfallsfreiheit postoperativ erreicht werden, wobei häufig eine invasive Ableitung der Insel notwendig ist [2, 7-9, 14,18,21]. Hierfür werden verschiedenste Techniken beschrieben, welche in dieser Übersichtsarbeit beleuchtet werden.…”
unclassified